2001
DOI: 10.1016/s0031-9422(01)00260-6
|View full text |Cite
|
Sign up to set email alerts
|

Halogenated metabolites with antibacterial activity from the Okinawan Laurencia species

Abstract: The chemical compositions of five species of the red algal genus Laurencia from coastal waters of Okinawa Prefecture, Japan, have been investigated. A halogenated C(15) acetogenin, (12E)-lembyne-A, was isolated from L. mariannensis, and a halogenated sesquiterpene, (6R,9R,10S)-10-bromo-9-hydroxy-chamigra-2,7(14)-diene, was first found from L. majuscula as a naturally occurring compound. Laurencia nidifica yielded previously known laurinterol and isolaurinterol. Samples of L. cartilaginea and L. concreta afford… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
61
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(67 citation statements)
references
References 26 publications
3
61
0
3
Order By: Relevance
“…Our result is in accordance with the antibacterial activity of Laurencia spp. reported from various geographic regions (DE NYS et al 1996, HELLIO et al 2001, TASKIN et al 2007) against marine, human and fish bacterial pathogens (VAIRAPPAN et al 2001(VAIRAPPAN et al , 2003BANSEMIR et al 2006). Based on the present findings L. brandenii could be utilized as renewable bioresource for the development of potential antimicrobials.…”
Section: Discussionsupporting
confidence: 63%
“…Our result is in accordance with the antibacterial activity of Laurencia spp. reported from various geographic regions (DE NYS et al 1996, HELLIO et al 2001, TASKIN et al 2007) against marine, human and fish bacterial pathogens (VAIRAPPAN et al 2001(VAIRAPPAN et al , 2003BANSEMIR et al 2006). Based on the present findings L. brandenii could be utilized as renewable bioresource for the development of potential antimicrobials.…”
Section: Discussionsupporting
confidence: 63%
“…It occurs mainly in the South Pacific and Indian Ocean, especially in Hawaii, and there is no record on its occurrence in China previously. Chemical investigation of L. nidifica for secondary metabolites started from 1974 [1] and the majority of these metabolites are halogenated sesquiterpenes and C 15 -acetogenins [2,3], many of which possess antimicrobial and antiviral activities [2,4]. In our continuing investigation on halogenated bioactive natural products from Laurencia species [5][6][7][8][9][10][11][12][13][14], we casually collected the species L. nidifica from Sanya coast of Hainan Province.…”
mentioning
confidence: 99%
“…A large number of these compounds have been obtained from Laurencia species having an intracellular, membrane-bound vesicles known as "corps en cerise" (cherry bodies) in the outer cell layer (the cortical layer) where, these inclusions are considered as a synthesis and/or storage sites of halogenated secondary metabolites [7]. On the other hand, Laurencia species without "corps en cerise" does not produce any halometabolites [8].…”
Section: Introductionmentioning
confidence: 99%
“…10% (w/w) from the ethanolic extract of L. microcladia [34]. Isoobtusol (26), described originally from L. obtusa [35], was isolated together with elatol (25) from L. majuscula in waters of Sabah, Malaysia and both compounds 25 and 26 were found to be active against some marine bacteria [8]. Vairappan et al reported significant antibacterial activity for compound 25 against Staphylococcus epidermis, Klebsiella pneumonia and Salmonella sp, whereas, isoobtusol was significantly active against K. pneumonia and Salmonella sp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation